Ideological Analysis in the Novel "Pulang" by Tere Liye: Critical Discourse Analysis of the Van Dijk Model - Yayah Ratna Sari Dewi; Teti Sobari (Journal of Educational Sciences, 2026)
This study investigates ideological representations in the Indonesian contemporary novel Pulang by Tere Liye through Teun A. van Dijk’s Critical Discourse Analysis (CDA) model. The research aims to reveal how language in the novel functions as a medium of ideology and social critique. Using a qualitative descriptive approach, the analysis focuses on macrostructure, superstructure, and microstructure to interpret selected textual excerpts. The findings demonstrate that Pulang conveys three dominant ideologies. First, moral humanism, which highlights honesty, self-awareness, and humanity as guiding values. Second, social nationalism, which emphasizes family, local traditions, and homeland as moral foundations. Third, anti-capitalism combined with spirituality, which critiques materialistic dominance and underscores the pursuit of inner peace. These ideologies position the novel not only as a literary narrative but also as a discourse that reflects social criticism and offers moral and spiritual insights. The study concludes that Pulang contributes to understanding how contemporary Indonesian literature articulates ideological perspectives in response to modern social challenges.